Training for the Elderly to Improve Skills in Preventing and Managing Chronic Diseases - Yuke Andriane; Santun Bhekti Rahimah; Miranti Kania Dewi; Siti Annisa Devi Trusda; Fajar Awaliya Yulianto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
An increasing elderly population in the world has a broad impact on society. Elderly people have different characteristics and are vulnerable to physical and psychological health problems, one of which is chronic diseases such as hypertension, diabetes, and coronary heart disease. The elderly require special attention from their families, surrounding communities, and the local government. In response to this, the Unisba Faculty of Medicine organized a Community Service (PKM) activity called